Implementation of School-Based Management in Improving the Quality of Learning in the City of Bekasi - Ade Mutiarawati (Future Science, 2021)
The importance of evaluating the implementation of School Based Management in providing innovative learning improvements in improving the quality of education, but the reality is that there are still elementary school educational institutions that do not know much about the benefits of implementing School-Based Management. The objectives of this study are 1) Determine the implementation of School-Based Management in improving the quality of learning; 2) Determine the factors supporting and inhibiting the implementation of School-Based Management in improving the quality of learning. Methods: The type of research used is descriptive qualitative research. The research data collection method was carried out by observation, interviews, and documents. Analysis of research data was carried out by presenting data, reducing, and drawing conclusions. The research location was conducted at one of the elementary schools in Bekasi City. Results: This study showed that 1) The implementation of school-based management was carried out through well-executed planning, organizing, implementing, and supervising management process by the essence of management in an autonomous, flexible, participatory, transparent and accountable manner; 2) Supporting factors, namely the role of the community, parents and committees in school activities, complete class teachers and almost all of them meet academic quality. Conclusion: The inhibiting factor is active, creative, effective, and fun learning which requires a lot of funds, time, and energy because it has to be prepared but in implementation, it can be handled properly.